REGIONAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF PRIMARY-ACTIVE TUBERCULOSIS IN THE REPUBLIC OF AZERBAIJAN - Aliyev, J.G. (World of Medicine and Biology, 2025)
In the Republic of Azerbaijan, zones with a high incidence of tuberculosis, pulmonary and extrapulmonary tuberculosis among patients initially registered in these zones over the past three years (2021–2023) were analyzed. It was found that the incidence rate was higher in the mountainous-foothill zone, which accounts for 43.0 % of the country’s territory. Thus, the incidence rate in zone II was 28.3 in 2021, which is 15.5 % higher than zone I and 26.9 % higher than zone III. The lowest incidence rate in 2022 was in the plain zone (22.9), and the highest was in the foothill-plain zone (32.1). This indicator is still the lowest in the plain zone (24 in 2023) and the highest in the foothill-plain zone (29.9). The number of patients initially registered in the foothill-plain zone over the last three years (2021–2023) accounts for more than half of the total number of patients initially registered in the country (51.5 %).